The Adweek Copywriting Handbook - Sugarman, Joseph (Ascent Audio, 2020)
Great copy is the heart and soul of the advertising business. In this practical guide, legendary copywriter Joe Sugarman provides proven guidelines and expert advice on what it takes to write copy that will entice, motivate, and move customers to buy. For anyone who wants to break into the business, this is the ultimate companion resource for unlimited success.